Position measurements at GNSS station SMR5 in 2023 with links to RINEX data files - Andrés F Zakrajsek; Ralf Krocker (PANGAEA, 2025)
SMR5 GNSS long-term raw-data series is aimed at contributing to the scientific research of Earth-System-involved global- as well as Antarctic-regional processes, improving International Terrestrial Reference Frame (ITRF) redefinitions, and benefiting society through enhanced GNSS-derived applications and services. The dataset was gathered at the Argentinean (Antarctic) research station San Martín in the year 2023. Approximate position in ITRF2014 frame at epoch 2023.5: X=927077.25m, Y=-2195043.59m, Z=-5896521.09m or in (GRS80) ellipsoidal coordinates: lat=68°07 extquotesingle46.850S, lon=067°06 extquotesingle11.599W, h=26.8m, orthometric height above EGM2008 geoid amounts 17.3m. GNSS receiver: TRIMBLE NetR9 (SN: 5226K50357), GNSS antenna: Zephyr Geodetic 2 w/Dome, PN: 57971-00 (SN: 30976593), Sampling interval: Originally 1 second, downsampled in postprocessing to 15 seconds. Each file covers a time period of one day. RINEX files have been converted from original TRIMBLE proprietary T02 files, applying software tools runpkr00 and teqc. RINEX format version is 2.11. Finally the data have been compressed applying Hatanaka tool (Hatanaka, Y. (2008), A Compression Format and Tools for GNSS Observation Data, Bulletin of the Geospatial Information Authority of Japan, 55, 21-30, available at https://www.gsi.go.jp/ENGLISH/Bulletin55.html) and gzip.
In: Schenke, Hans Werner; Zakrajsek, Andrés F; Vey, Sibylle; Krocker, Ralf (2012): Position measurements at GPS station SMR5 [dataset publication series]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.770301